THE IMPLEMENTATION OF INFORMATION GAP ACTIVITY AND JUMBLED SENTENCE GAME IN TEACHING READING COMPREHENSION - Patty, Galfry; Wardani, Rizqi Claudia; Nurteteng, Nurteteng (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
The implementation of Information Gap Activity and Jumbled Sentences Game in Teaching Reading Comprehension at Eight Grade Smp Muhammadiyah 2 Mariyai Sorong Regency Thesis English Education Department faculty of language social and sport education university of pendidikan muhammadiyah sorong,May 2023.The objective of this research is to know whether the implementation of information gap Activity and jumble sentence game has impact or not on students’ reading at smp muhammadiyah 2 mariyai sorong regency. The research used pre-experimental quantitative research design with design is one group pretest-posttest. The population of this research was the eighth grade students’ at Smp Muhammadiyah 2 Mariyai Sorong Regency . The researcher chose this class because there are some problems with students' reading. In the collecting data researcher used multiple choice with 20 questions for the pretest and posttest. To analyze the data the researcher uses the SPSS 20 version. The result finding of the research showed that the result of pair sample T test(0,00) the categorized was impact .In addition to the result of the pair sample T-test is P value (0.00)<(0,05).it means that HO was rejected and Ha was accepted. The alternative hypothesis (Ha) was there is an impact in teaching reading using information gap and jumbled sentence games.